Herbal medicines from ginkgo leaf extract in the treatment of mild dementia - Petrović, Silvana; Ušjak, Ljuboš (Archives of Pharmacy, 2020)
According to current EU monograph of the Committee on Herbal Medicinal Products of European Medicines Agency (EMA/HMPC) for ginkgo leaf, Ginkgonis folium (Ginkgo biloba, Ginkgoaceae), herbal medicines prepared from refined and quantified dry extract of ginkgo leaf are used for the improvement of (age-associated) cognitive impairment and of quality of life in mild dementia. It was demonstrated in clinical trials that long-term use of the extract is effective mainly in patients more than 50 years old. The precise mode of action is not known. According to Ph. Eur., the extract should contain 22.0-27.0% of flavonoids, 2.8-3.4% of ginkgolides A, B and C, and 2.6-3.2% of bilobalide, which are active constituents, and maximum 5 ppm of ginkgolic acids, which are potential allergens. These herbal medicines are characterized by corresponding posology, duration of use, contraindications, special warnings, and precautions for use, interactions and possible undesirable reactions.
Keywords: Ginkgo biloba; leaf extract; mild dementia; herbal medicines; efficacy and safety